Breastfeeding pathologies: analysis of prevalence, risk and protective factors - Govoni, Laura; Ricchi, Alba; Molinazzi, Maria Teresa; Galli, Maria Cristina; Putignano, Angela; Artioli, Giovanna; Foà, Chiara; Palmieri, Elisabetta; Neri, Isabella (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: Breastfeeding is essential for the health of mothers and newborns, and it is recommended by WHO-UNICEF as the sole source of nutrition and protection for the first 6 months of life and beyond. In order to fully promote this practice, it is important to recognize early conditions that can lead to pathological breastfeeding. Aim: The study aims to analyze the prevalence and the possible risk or protective factors concerning the pathology of breastfeeding. Methods: For this observational study were consulted the medical records and the files of the Breastfeeding clinic of 1065 puerperal women, of the University Hospital of Modena, from January to August 2016. The data were processed with the SPSS Software. Results: In our study population, 532 (50%) puerperal women presented a breastfeeding-related disease, of which 330 (31%) had a disease affecting the mother (breast engorgement, fissures, a-/hypo-galactia, discontinuation of breastfeeding, galactocele, mastitis and candidiasis), 105 (9.9%) of the newborn (inadequate suction, neonatal jaundice, pathological weight loss, need for admission to NICU) and 97 (9.1%) of both the mother and the newborn. Discussions: It is evident from the results that the predicting factors of pathology in breastfeeding are present in pregnant women who give birth in an early gestational age and with high age, birth rate and nationality. Conclusions: staff training courses are essential to respond to WHO-UNICEF recommendations and to improve the continuity of care for the mother-child dyad.